Fe-porphyrin carbon matrix as a bifunctional catalyst for oxygen reduction and CO2 reduction from theoretical perspective. (18th July 2019) - Liu, Shize; Cheng, Lin; Wang, Wencheng; Li, Kai; Wang, Ying; Wu, Zhijian
ABSTRACT: The oxygen reduction reaction (ORR) and carbon dioxide reduction reaction (CO2 RR) have attracted worldwide attention in order to solve the energy crisis and global warming. In this work, we have investigated the ORR and CO2 RR activity of Fe-porphyrin carbon material (FeN4 -C) by using the density functional method. The catalytic active sites are identified based on the charge transfer analysis and it is found that FeN4 moiety and its adjacent eight C atoms are the active centre. ORR proceeds via a four-electron process. The OOH hydrogenation into O + H2 O is the most favourable pathway with the rate-determining step to be the formation of OOH. The energy barrier is 0.09 eV, much smaller than 0.56 eV for FeN4 doped graphene and 0.80 eV for pure Pt. The predicted working potential is 0.52 V, larger than 0.35 V for FeN4 doped graphene. For CO2 RR, CO2 tends to be reduced to HCHO and CH3 OH with the limiting potential of −0.62 V. HCOOH is the minor product. In a word, the above results suggested that FeN4 -C is a promising bifunctional electrocatalyst for both ORR and CO2 RR. GRAPHICAL ABSTRACT: